2021
DOI: 10.1080/1828051x.2021.1929523
|View full text |Cite
|
Sign up to set email alerts
|

Predicting atmospheric cadmium and lead using honeybees as atmospheric heavy metals pollution indicators. Results of a monitoring survey in Northern Italy

Abstract: Tangorra (2021) Predicting atmospheric cadmium and lead using honeybees as atmospheric heavy metals pollution indicators. Results of a monitoring survey in Northern Italy,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…For instance, Zarić et al (2022) and Van Der Steen et al (2012) reported lower and higher As content respectively. For Pb, Perugini et al (2011) and Costa et al (2021) reported lower and higher mean values respectively. For Hg, Sadeghi et al (2012) and Toporcák et al (1992) reported higher mean Hg values.…”
Section: Discussionmentioning
confidence: 93%
“…For instance, Zarić et al (2022) and Van Der Steen et al (2012) reported lower and higher As content respectively. For Pb, Perugini et al (2011) and Costa et al (2021) reported lower and higher mean values respectively. For Hg, Sadeghi et al (2012) and Toporcák et al (1992) reported higher mean Hg values.…”
Section: Discussionmentioning
confidence: 93%
“…Тому актуальним є питання виробництва екологічно безпечних продуктів бджільництва. Адже продукції медоносних бджіл належить чільне місце в життєдіяльності людини (Matin et al, 2016;Didaras et al, 2020;Costa et al, 2021;Ricigliano et al, 2021;El-Seedi et al, 2022). До якісних показників продукції медоносних бджіл ставляться дуже високі вимоги, оскільки нині Україна стала основним експортером медів у Європу.…”
unclassified
“…У всьому світі ведуться пошуки засобів біоіндикації екологічного стану довкілля (Komarova, 2018;Costa et al, 2021;Di Fiore et al, 2022). Це пов'язано з тим, що важкі метали, як і інші забруднювачі навколишнього середовища, мають неоднаковий рівень переходу із ґрунту в кореневу систему, з кореневої системи у стебло, із стебла в суцвіття й із суцвіття в пилок і нектар.…”
unclassified